Workplace mindfulness-based programmes for stress and wellbeing: a realist review and evaluation - Micklitz, K (2022)
Mindfulness-based programs (MBPs) are increasingly offered in the workplace to reduce stress and enhance wellbeing. A growing body of evidence suggests that these programmes can be beneficial; however, dropout rates are often high, and there is great heterogeneity in both programme content and strength of effects between studies. This thesis contributes to a better understanding of what makes these programmes successful, under what circumstances, for whom, and why. A realist approach was employed that is theory-driven and well-suited to make sense of complex interventions, such as MBPs.